EKSPLORASI FAKTOR BELIEFS DAN ATTITUDES: KAJIAN TERHADAP SOCIAL JUDGEMENT THEORY DI ERA MEDIA DIGITAL - Boer, Rino F.; Lesmana, Dionisius (Bricolage : Jurnal Magister Ilmu Komunikasi, 2018)
Globalization encourages foreign brands to come to Indonesia, one of them is Keds as asneakers shoe brand. One of the problems that Keds faces when it comes to Indonesia is the perceptionabout Keds as a type of shoes even though actually it is a brand of shoes. Therefore, Keds held a “LadiesFirst Since 1916” Campaign not only to celebrate their 100th anniversary, but also to create awarenessabout Keds as the first sneakers brand for ladies since 1916 and to deliver their persuasive messagesthrough promotion activites in the campaign. The aim of this research is to find out Keds customer buyingdecision process based on social judgement theory, where the customer will interpret the persuasivemessages about the promotion activities in the campaign and also to find out the stages of customerdecision buying process. The research method that was used is qualitative descriptive method throughindepth interview with Keds customers. The result shows that the interpretation of the messages throughattiudes/cognitive and beliefs/mental ego involvement is in latitude of acceptance that leads inassimilation effect and it seen in evaluation of alternatives stage in the buying decision process by Kedscustomer.Keywords: buying process, beliefs, attitudes, persuasive